Characteristics of ERP software maintenance: A multiple case study - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2001)
A multiple case study approach was employed to identify maintenance activities pertaining to enterprise resource planning (ERP) implementation, classify them into maintenance categories, and assess their relative frequency at various stages of the ERP maintenance lifecycle. Five maintenance categories (corrective, adaptive, perfective, preventive, user support) were identified from a review of the literature on software maintenance. A new category pertaining to ‘communication, coordination and knowledge exchange with external parties’ and herein labeled ‘external parties’ is introduced to highlight the supporting role of external parties in ERP maintenance. This category includes reporting problems to vendors and consultants, tracking their progress towards problem resolution, and coordinating work and relations with vendors, consultants, and external user-organizations. This study also highlights some differences between maintenance trends of ERP versus traditional systems.